Present status and future prospects of Ber ( Ziziphus mauritiana Lamk.)-A review (IASH Indian Journal of Arid Horticulture, 2025)
Ber (Ziziphus mauritiana Lamk.) is one of the hardy fruits that can be profitably cultivated in arid and semi-arid conditions, where most other fruit trees fail to grow due to lack of irrigation and other environmental constraints. It is mainly cultivated for its fresh fruits and rightly called as poor man’s apple due to its high nutrition al value i.e. higher protein (0.8 g), β-carotene (70 IU), vitamin C (50-100 mg) and medicinal value. In North India, ber flowers in the month of August-September. It mainly produces heavy flowers in the auxiliary cymes on maturation, and current season’s growth with very high fruit set percentage. It can be processed to prepare various value added products i.e. murabba, pulps, jam, candies and beverage. The best method of commercial propagation is by budding and the widely adopted is shield budding (T or I budding). Recently success in micro propagation of ber has also been achieved and the best explant for in vitro micro propagation is stem from mature tree. Due to its ability to withstand adverse climatic conditions, it is truly a “desert apple” or “king of arid fruits” and can be profitable grown by farmers of arid and semi-arid regions of India.